Penerapan Location Based Service (LBS) dan QR Code Detection pada Aplikasi Pemetaan dan Penjemputan Retribusi Parkir Kendaraan Berbasis Android - Dwi Novia Prasetyanti; Purwanto, Riyadi; Rostika Listyaningrum (Infotekmesin, 2023)
One source of regional income for Cilacap Regency is the management of vehicle parking lots. Currently, parking area management is carried out by recording the identity of the parking location based on the street name, while the withdrawal of parking fees is carried out by towing officers who come to the parking location and then record it in a book. The current management of parking lots is still inaccurate because there are several street names that have more than one parking area which results in data redundancy. The conventional parking fee collection system causes frequent discrepancies in reports due to the potential for misuse of parking fees. The absence of tools that can be used by related agencies to control reports is the cause of the problem. The research objective is to develop an information system by applying LBS technology which functions to detect parking points precisely and QR Code Detection which functions to detect the identity of parking attendants. System development uses the ADDIE model. The results of the research are an information system for mapping parking lots and picking up parking fees based on Andorid which can help manage vehicle parking lots which includes mapping the location of parking lots and picking up vehicle parking fees.